2024
DOI: 10.1038/s41598-024-60463-2
|View full text |Cite
|
Sign up to set email alerts
|

Predicting postoperative rehemorrhage in hypertensive intracerebral hemorrhage using noncontrast CT radiomics and clinical data with an interpretable machine learning approach

Weigong Wang,
Jinlong Dai,
Jibo Li
et al.

Abstract: In hypertensive intracerebral hemorrhage (HICH) patients, while emergency surgeries effectively reduce intracranial pressure and hematoma volume, their significant risk of causing postoperative rehemorrhage necessitates early detection and management to improve patient prognosis. This study sought to develop and validate machine learning (ML) models leveraging clinical data and noncontrast CT radiomics to pinpoint patients at risk of postoperative rehemorrhage, equipping clinicians with an early detection tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…In the task of ECG signal classification, deep learning models, especially CNNs, have demonstrated their high efficiency [1][2][3]18]. However, the decision-making processes of these models often lack transparency, widely referred to as the "black box" problem [6,25,26]. For the end-users of the models, including physicians and clinical experts, understanding the internal workings and decision logic of the models is crucial [27].…”
Section: Interpretability Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the task of ECG signal classification, deep learning models, especially CNNs, have demonstrated their high efficiency [1][2][3]18]. However, the decision-making processes of these models often lack transparency, widely referred to as the "black box" problem [6,25,26]. For the end-users of the models, including physicians and clinical experts, understanding the internal workings and decision logic of the models is crucial [27].…”
Section: Interpretability Analysismentioning
confidence: 99%
“…In the domain of ECG signal classification, SHAP value analysis has proven to be a powerful tool for identifying and interpreting key features that affect model predictions [7]. Existing studies have shown that SHAP values play a significant role in recognizing crucial frequency features in ECG signals, predicting ST-segment elevations for cardiac events, and offering other diagnostic insights [5,6,[25][26][27]. For instance, Rashed-Al-Mahfu et al [30] successfully demonstrated the effectiveness of SHAP value analysis in identifying key frequency features that impact ECG signal classification.…”
Section: Comparison With Existing Workmentioning
confidence: 99%